Curricular Innovation for Food Security - Irma Cecilia Castillo Escalante; Adán Guillermo Ramírez García (MDPI AG, 2023)
The curriculum is a dynamic and continuous process that must be adapted to the requirements and needs of specific contexts to respond to current problems. Currently, it is estimated that more than 828 million people in the world suffer from hunger, so food security must be based on the production and availability of food and physical and economic access to food, as well as its safety. For the above, this research aims to propose a curricular innovation to the professional competences of the study program of the Agricultural Technician (TAP) that is offered in the Agricultural Technological Baccalaureate Centers to train technicians who contribute to food security in the region. A methodology with a mixed perspective with a qualitative approach and descriptive exploratory character was used. Based on the primary information and data collection, it was possible to specify and substantiate a curricular proposal according to the training needs of specialized technicians, who develop professional skills to promote food security, the establishment of agricultural production system, management of livestock production systems, operation of agro-industrial production system, and the design and execution of projects to promote the cultivation of food from small-scale families.